Preference of Coping Strategies during Stressful Situations among General People - Adhikari, Upasana (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2023)
The sensation of being overburdened, anxious, or exhausted is a common description of stress. People of all ages, genders, and circumstances can be impacted by stress, which can result in problems with their physical and mental health. At times, a little stress can be good for you. Extreme stress, however, can have negative effects on the immunological, cardiovascular, neuro-endocrine, and central neurological systems. Extreme stress can also have a devastating emotional impact. Minor episodes of stress can be managed by using one's body's inherent defenses to adjust to shifting circumstances, but persistent, excessive stress that lasts for a lengthy period of time can be physically and psychologically crippling. Coping can be defined as those thoughts and actions which we deal with a threatening situation. Coping strategies can be of various types, among which most common types are: Problem focused coping strategy, Seeking Social support coping strategy, Passive acceptance coping strategy, Avoidance coping strategy, Religious Coping strategy and Emotion focused coping strategy. This study was based on survey method technique from few sites of Kathmandu valley. Data is in quantitative nature. The questionnaire of socio-demographic variables and coping strategy was distributed among 302 participants for quantitative data. People were selected conveniently during this study. Coping check list developed by Rao, Subbakrishna and Prabhu was used for this study. In this research it was found that, for preference of type of coping strategy by total number of respondents, problem focused coping strategy had the maximum score whereas religious coping strategy had its minimum score.